Physicians' attitude towards community pharmacists' contribution in the treatment decision making - Rebar Ali Mohammed; Bushra Hassan Marouf (Universidade de São Paulo, 2023)
Abstract A collaborative physician-pharmacist relationship is a fundamental component of a patient's primary care. The aim of this study was to investigate the attitude of physicians toward collaborative work with community pharmacists in Sulaimani City, Iraq. A cross sectional design was utilized, and a questionnaire was sent to 60 physicians, of whom 47 completed the questionnaire. A total of 26 (55.3%) physicians stated that they had a history of collaboration with pharmacists in their routine daily work. During/before the treatment process, more than one-third of the physicians "rarely" practiced collaboratively, and one-fifth "never" collaborated. There was little agreement on the community pharmacist's recommendations; however, after the treatment decision by the physician, a higher degree of agreement was reported, and the number of physicians who were "rarely" or "never" practiced collaboratively decreased to less than 5%. Furthermore, the physicians' perspective on the pharmacists' role showed that advising patients on drug administration (85.1%) and preventing drug interactions (76.6%) were the most common duties of the community pharmacists. Physicians agreed on several barriers with respect to collaboration with pharmacists. In conclusion, the physicians' perspective on the engagement of the community pharmacist in the management of patients was relatively limited. The pharmacist's recommendation was more accepted after medications were prescribed than before or during decision making on the treatment.